PELAKSANAAN PEMBELAJARAN SENI BUDAYA (TARI )KELAS VIII DI MTSN 3 KOTA PADANG - Reza Kurnia Putri; Susmiarti (Universitas Negeri Padang, 2025)
This research aims to observe and describe the learning of Cultural Arts (dance) for class VIII.2 at MTs N 3 Kota Padang. This type of research is qualitative with a descriptive method. The research instrument is the researcher themselves, assisted by writing tools and a camera. Data was collected through literature review, observation, interviews, and documentation. The steps for analysing data are collecting data, identifying data, classifying data, describing data, and concluding data. The research results indicate that the implementation of Cultural Arts (dance) learning for Class VIII.2 at MTsN 3 Kota Padang is carried out in 3 stages, namely the planning stage, implementation, and evaluation. In terms of lesson planning, it has been prepared by the teacher in accordance with the independent curriculum, and the teacher has developed learning materials such as teaching modules and content tailored to the characteristics of the students. Planning also includes determining learning objectives, material to be taught, methods used, and assessment to be conducted. The implementation of dance art education takes place in three stages, namely the introductory, core, and closing activities. In this activity, the teacher still uses traditional methods such as lecturing, demonstrations, and direct practice that actively involve students. The learning environment is quite conducive although there are still some challenges, such as time limitations, media, and differences in students' abilities to absorb movement material. Evaluation is carried out continuously, covering summative and formative assessments. Teachers assess students' understanding of the dance material, students' attitudes during the learning process, and students' skills in practicing dance movements. Evaluation is done through observation, individual and group assignments, as well as dance performances as a form of practical examination.